Economic development strategies in the Dominican Republic - Susan Pozo; José R. Sánchez-Fung; Amelia U. Santos-Paulino (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
The paper documents the economic development strategies pursued by the Dominican Republic. The study argues that the country's success results from the implementation of a three-pronged economic development strategy. The first prong relates to diversifying production and the second to developing special economic zones. These zones operate in parallel fashion to the rest of the economy but with protections from domestic impediments to growth and progress. The third item in the recipe involves maintaining ample economic and social engagement with the rest of the world. The paper also highlights challenges that the country faces going forward.
Keywords: O2; O54; 330; economic development strategies; primary commodities; special economic zones; economic openness; Dominican Republic; Entwicklungsstrategie; Dominikanische Republik